PENILAIAN KESEHATAN TAHURA BANTEN PADA BLOK KOLEKSI TUMBUHAN DAN ATAU SATWA - Nur Rohman; Slamet Budi Yuwono; Gunardi Djoko Winanrno; Sugeng P. Harianto; Agus Setiawan; Rahmat Safe’i (Forestry Study Program University Of Mataram, 2023)
Banten Forest Park is one of the conservation areas with an area of 1,595.9 ha whose management is divided into five large blocks, one of which is a collection block of plants and or animals. Tahura Banten has the potential to have a fairly high economic and ecological value, it needs an important role in knowing the current forest conditions that allow for changes and trends in it by conducting forest health assessments. Tahura health can be assessed through biodiversity in a Region of Tahura identified as the criteria for the sustainability of forest ecosystems. The purpose of this study is to conduct a health assessment of Tahura Banten on the Plant and or Animal Collection Block which is intended to assess and report the current health condition (status) of Tahura based on ecological indicators of forest health. This research was conducted in November to December 2021 at the Plant and or Animal Collection Block in Tahura Banten. Data collection is carried out by creating a tahura health measurement plot using the Forest Health Monitoring method. Analysis of ecological indicators used in this study in the form of biodiversity, vitality (header conditions) and productivity. The results of data processing resulted in the value of the diversity status of tree types (H'), header conditions (VCRs), and productivity (LBDS) in 10 (ten) plot clusters. Tahura's health category is obtained based on the final value. The results of the data obtained can be categorized as 30% good, 40% moderate and 30% bad health conditions. The results of this study showed that the value of Tahura Health is in a moderate condition with a threshold value of 4,187-5,692 of 40%, which is able to define Tahura Banten in the Plant and or Animal Collection Block has a fairly healthy condition.